Counseling Regarding Stunting Prevention and The Benefits Of Mackerel For Improving Mother's Attitude In Giving Food High Protein For Toddler - Anna, Nurjannah; Asjur, Asti Vebriyanti; Jusriani, Rini (Borneo Community Health Service Journal, 2023)
Stunting is a public health problem that must be treated seriously. Indonesia is one of the countries with the fifth largest stunting prevalence rate. Stunting occurs starting in the womb and only becomes visible when the child is two years old. Counseling is one strategy that can be carried out to increase knowledge and change the attitudes of mothers who have toddlers so that they can provide the right food for toddlers to prevent stunting from an early age. The aim of this community service activity is to provide education about preventing stunting and the benefits of mackerel for toddlers to improve mothers' attitudes in preventing stunting and providing fish as a high-protein food for toddlers. The method used is counseling and question and answer between participants and government officials. The results of this service activity are proven by the participants' activeness in the activity and the increasing attitude of mothers in providing fish-based food for toddlers according to the results of pretest and posttest measurements. The results of this activity have been able to improve mothers' attitudes to prevent stunting in toddlers.